The Influence of Motivation, Physical Work Environment, and Job Satisfaction on Employee Performance in the Rehabilitation Center Work Unit of the Ministry of Defense of the Republic of Indonesia - Retnowati Wibowo, Diah Ayu; Khaerudin (Dinasti International Journal of Digital Business Management, 2025)
This study analyzes the influence of work motivation, physical work environment, and job satisfaction on employee performance in the Rehabilitation Center Work Unit of the Ministry of Defense of the Republic of Indonesia (Satker Pusrehap Kemhan RI). A quantitative approach with descriptive and causal associative methods was used. Data were collected through questionnaires distributed to 49 employees selected via random sampling. The analysis employed multiple linear regression with a t-test for hypothesis testing. The results showed that work motivation, physical work environment, and job satisfaction significantly influence employee performance. Partial hypothesis testing found that work motivation (t = 2.504 > 2.012), physical work environment (t = 3.514 > 2.012), and job satisfaction (t = 2.786 > 2.012) had significant effects. Simultaneous testing revealed that work motivation and job satisfaction together significantly influence performance (F = 2.506 > 1.83, p = 0.006 < 0.05). This study highlights the importance of enhancing work motivation, optimizing the work environment, and improving job satisfaction to boost employee performance. A human resource management strategy focusing on these factors is essential for increasing organizational effectiveness.